Mastering the business of global trade negotiating competitive advantage contractual best practices, Incoterms®, and leveraging supply chain options - Cook, Thomas A. 1953- (The global warrior series, 2014)
Mastering the Business of Global Trade: Negotiating Competitive Advantage Contractual Best Practices, Incoterms, and Leveraging Supply Chain Options explains the key elements any international business person must know, but more importantly, it also describes how to use negotiation skills, leveraged options, and Incoterms to extract the maximum benefits from your supply chain